A cool-water bryozoan association from the La Pola Formation (Sandbian, Ordovician) of Argentine Precordillera - Ernst, Andrej (2022)
Nineteen bryozoan species belonging to 18 genera are described from the La Pola Formation (Sandbian, Upper Ordovician) of Argentine Precordillera. Two trepostome genera each with one new species, respectively, are new: Albardonia bifoliata n. gen., n. sp. and Argentinopora robusta n. gen., n. sp. Five more species are new: a cystoporate Xenotrypa argentinensis n. sp., two trepostomes Heterotrypa enodis n. sp. and Nicholsonella spinigera n. sp., as well as two ptilodictyines Pseudostictoporella simplex n. sp. and Chazydictya ornata n. sp. The studied fauna shows some connection with Laurentia and Baltica on the species level and is similar to Siberia on the generic level. Furthermore, the generic composition of the La Pola fauna is similar to contemporary faunas of Las Aguaditas and Las Plantas formations of the Argentine Precordillera. The described fauna comes from mixed carbonate-siliciclastic deposits and represents a largely para-autochthonous association, with few autochthonous elements. The bryozoan growth forms indicate shallow shelf conditions. Bryozoans are associated with brachiopods, red algae, and echinoderms indicating heterozoan community typical for temperate to cool water environments with high primary production.